Ten-year progression of myopic maculopathy: the Beijing Eye Study 2001-2011 - Yan, Yan Ni; Jonas, Jost B. (Ophthalmology, 2018)
Purpose - To investigate the progression pattern of myopic maculopathy and associated factors in a population-based study. - Design - Population-based longitudinal study. - Participants - The Beijing Eye Study including 4439 participants in 2001 was repeated in 2011, with 2695 individuals (66.4%) being re-examined in 2011. - Methods - The study participants underwent detailed ophthalmic and general examinations. Using fundus photographs obtained in 2001 and 2011, we assessed the progression of myopic maculopathy in highly myopic eyes with a refractive error ≥−6 diopters in 2001. Myopic maculopathy was differentiated into tessellated fundus (category 1), diffuse chorioretinal atrophy (category 2), patchy chorioretinal atrophy (category 3), and macular atrophy (category 4), with lacquer cracks and choroidal neovascularization as additional plus signs. - Main Outcome Measures - Progression pattern of myopic maculopathy. - Results - Of 110 highly myopic eyes (70 individuals) at baseline, 39 eyes (35.5%) showed progression observed in 15 of 79 eyes (19%) with tessellated fundus at baseline, in 17 of 24 eyes (71%) with diffuse chorioretinal atrophy, in all 6 eyes with patchy chorioretinal atrophy, and the 1 eye with macular atrophy. Lacquer cracks detected in 2 eyes in 2001 developed into a small patchy atrophy (1 eye) or widened during the follow-up (1 eye). Five eyes demonstrated new lacquer cracks. In binary regression analysis, progression of myopic maculopathy was associated with longer axial length (P < 0.001; odds ratio [OR], 7.13; 95% confidence interval [CI], 2.49-20.4), older age (P = 0.001; OR, 1.25; 95% CI, 1.10-1.42), higher prevalence of staphylomas (P = 0.03; OR, 24.3; 95% CI, 2.89-204), smaller parapapillary γ-zone in 2011 (P = 0.01; OR, 0.61; 95% CI, 0.41-0.91), and female gender (P = 0.04; OR, 9.78; 95% CI, 1.06-90.6). - Conclusions - The 10-year progression rate of myopic maculopathy in this elderly Chinese population was 35.5%, increasing from 15 of 79 eyes (19%) in category 1 of myopic maculopathy at baseline to 17 of 24 eyes (71%) in category 2 and 6 of 6 eyes (100%) in category 3. Risk factors for myopic maculopathy progression were longer axial length, pre-existing staphylomata, smaller parapapillary γ-zone, older age, and female gender.
Gesehen am 15.12.2020